Prognostic factors of poor postoperative outcomes in gastrectomies - Stüben, B. O.; Plitzko, G. A.; Stern, L.; Li, J.; Neuhaus, J. P.; Treckmann, J. W.; Schmeding, R.; Saner, F. H.; Hoyer, D. P. (Frontiers in Surgery, 2023)
Background Gastric cancer is one of the most common cancers worldwide and is the third most common cause of cancer related death. Improving postoperative results by understanding risk factors which impact outcomes is important. The current study aimed to compare immediate perioperative outcomes following gastrectomy. Methods 302 patients following gastric resections over a 10-year period (January 2009–January 2020) were identified in a database and retrospectively analysed. Epidemiological as well as perioperative data was analysed, and a univariate and multivariate analysis performed to identify risk factors for in-hospital mortality. Results In general, gastrectomies were mainly performed electively (total vs. subtotal 95% vs. 85%, p = 0.004). Patients having subtotal gastrectomy needed significantly more PRBC transfusions compared to total gastrectomy (p = 0.039). Most emergency surgeries were performed for benign diseases, such as ulcer perforations or bleeding and gastric ischaemia. Only emergency surgery was significantly associated with poorer overall survival (HR 2.68, 95% CI 1.32–5.05, p = 0.003). Conclusion In-hospital mortality was comparable between total and subtotal gastrectomies. Only emergency interventions increased postoperative fatality risk.